2014
DOI: 10.1007/s11605-013-2446-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Delayed Gastric Emptying After Pylorus-Preserving Pancreatoduodenectomy with Antecolic Reconstruction, a Long Jejunal Loop, and a Jejuno-Jejunostomy

Abstract: The results of this retrospective study suggest that the antecolic route with a long jejunal loop and Braun's anastomosis minimizes DGE rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 41 publications
1
25
0
3
Order By: Relevance
“…Eleven eligible studies were determined through applying our inclusion criteria. 3 , 13 , 14 , 17 24 Two of 11 were reported by the same institute and the same first author. 20 , 24 Only 1 with more detailed data was selected 20 to avoid statistical bias because of duplicate counting (Figure 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…Eleven eligible studies were determined through applying our inclusion criteria. 3 , 13 , 14 , 17 24 Two of 11 were reported by the same institute and the same first author. 20 , 24 Only 1 with more detailed data was selected 20 to avoid statistical bias because of duplicate counting (Figure 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…The Braun jejunojejunostomy is thought to be an important procedure for reducing the risk of DGE [12, 33]. Because the Braun jejunojejunostomy can reduce the pressure in the biliopancreatic limb, it may decrease stimulation to the pressure receptors of the gastrointestinal tract, thereby decreasing the incidence of DGE.…”
Section: Discussionmentioning
confidence: 99%
“…The possible factors associated with DGE include antroduodenal ischemia [35], postoperative intra-abdominal complications [1, 5, 6, 27, 36, 37], low plasma motilin concentration [3, 38], and technical factors such as torsion or angulation of the digestive tract reconstruction [32, 33, 39]. Among the several possible factors of DGE, the most important are postoperative intra-abdominal complications like pancreatic fistula, biliary fistula, and intra-abdominal abscess [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we found that the gastrin G-17 level was significantly increased compared to that before the surgery instead of being decreased, and its mechanisms were still not clear. G-17 has important roles in gastrointestinal hormones [17], and this also demonstrated the necessity of retaining the gastric antrum.…”
Section: Discussionmentioning
confidence: 99%